A polishing liquid for chemical mechanical polishing and a chemical mechanical polishing method
By using a specific composition polishing liquid in the chemical mechanical polishing process of Cu/Co interconnect structures to adjust the concentration and combination of corrosion inhibitors, the problems of defects such as surface roughness, dish shape and corrosion pit in the prior art are solved, and a more efficient metal surface planarization and removal effect is achieved.
Patent Information
- Application Number
- CN202310253838.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The prior art is difficult to effectively remove excess copper film and barrier layers in Cu/Co interconnection structures, resulting in the occurrence of defects such as surface roughness, dish shape and corrosion pits.
A polishing liquid including abrasives, oxidants, corrosion inhibitors, complexing agents and water is adopted. The corrosion inhibitor is composed of 1,2,4-triazole, potassium oleate or 1-phenyl-5-mercaptotetraazole. By adjusting the concentration and combination of the corrosion inhibitor, the polishing rate selection ratio of Cu/Co is controlled, so as to reduce surface corrosion and improve the metal surface planarization quality.
It effectively reduces surface corrosion, improves the flattening quality of metal surfaces, and prevents the occurrence of defects such as surface roughness, disc shape and corrosion pits during polishing.
Smart Images

Figure CN116240550B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wafer production, and in particular relates to a polishing liquid for chemical mechanical polishing and a chemical mechanical polishing method. Background Art
[0002] The integrated circuit industry is the core of the information technology industry and plays a key role in promoting the transformation and upgrading of the manufacturing industry to digitalization and intelligence. Chips are the carriers of integrated circuits. Chip manufacturing involves chip design, wafer manufacturing, wafer processing, electrical measurement, cutting packaging and testing. Among them, chemical mechanical polishing (CMP) is one of the five core processes in the wafer manufacturing process. Chemical mechanical polishing is an ultra-precision surface processing technology for global flattening. The whole process is an alternation of chemical and mechanical actions, and finally the polishing of the wafer surface is completed.
[0003] In the back-end process of integrated circuit manufacturing, the main purpose of CMP process for Cu interconnect structure is to remove excess copper film and the barrier layer under the copper film while ensuring global planarization, so as to achieve complete insulation between Cu interconnect wiring. Polishing of barrier layer, as the last CMP process of copper interconnect structure, plays a decisive influence on the final global planarization effect of wafer.
[0004] Co has certain advantages as a barrier layer in terms of failure temperature and duration, and its resistivity is low, which can also realize an ultra-thin barrier layer structure. At present, the CMP polishing research of Cu / Co interconnect structure is still in a relatively early stage, and most polishing liquids for metal cobalt are not suitable for the CMP process of the barrier layer of Cu / Co interconnect structure. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a polishing liquid for chemical mechanical polishing and a chemical mechanical polishing method.
[0006] In a first aspect, an embodiment of the present invention provides a polishing liquid for chemical mechanical polishing, the polishing liquid comprising an abrasive, an oxidant, a corrosion inhibitor, a complexing agent and water;
[0007] Wherein, the corrosion inhibitor includes any one of 1,2,4-triazole, potassium oleate or 1-phenyl-5-mercaptotetrazole or a combination of at least two thereof.
[0008] In some embodiments, the complexing agent includes any one of citric acid (CA), glycine or (GLY) ethylenediaminetetraacetic acid (EDTA) or a combination of at least two thereof.
[0009] In some embodiments, the complexing agent is ethylenediaminetetraacetic acid, and the corrosion inhibitor is 1-phenyl-5-mercaptotetrazolyl.
[0010] In some embodiments, the concentration of the corrosion inhibitor is 1-7 mM.
[0011] In some embodiments, the corrosion inhibitor consists of 1-phenyl-5-mercaptotetrazole and potassium oleate.
[0012] In some embodiments, the concentration ratio of 1-phenyl-5-mercaptotetrazole to potassium oleate is 1:(1-5).
[0013] In some embodiments, the oxidizing agent is potassium persulfate.
[0014] In some embodiments, the pH value of the polishing liquid is 9.5-11.
[0015] In a second aspect, an embodiment of the present invention provides a chemical mechanical polishing method, the chemical mechanical polishing method comprising:
[0016] The polishing liquid is spread on the surface of the polishing pad, the carrier head presses the wafer onto the polishing pad and drives the wafer to rotate, and the copper interconnection cobalt barrier layer structure of the wafer is chemically mechanically polished under the action of the polishing liquid.
[0017] In some embodiments, during the chemical mechanical polishing process, the rotation speed of the polishing pad is 90-100 rpm, and the rotation speed of the carrier head is 80-90 rpm.
[0018] Compared with the prior art, the beneficial effects of the present invention include:
[0019] The present invention adds a corrosion inhibitor of specific components and concentrations into the polishing liquid, so that the polishing rate selection ratio of Cu / Co is in an adjustable state, so as to reduce surface corrosion, improve the metal surface flattening quality, and prevent the occurrence of defects such as surface roughness, dishing and corrosion pits during the polishing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The advantages of the present invention will become clearer and easier to understand through the detailed description made in conjunction with the following drawings, which are only schematic and do not limit the scope of protection of the present invention, wherein:
[0021] Figure 1 The Tafel curves and impedance spectra of Cu and Co in TAZ of different concentrations provided by Examples 1-4 of the present invention are shown;
[0022] in, Figure 1 (a) Tafel curves of Cu in different concentrations of TAZ provided by Examples 1-4 of the present invention;
[0023] Figure 1 (b) Tafel curves of Co in different concentrations of TAZ provided by Examples 1-4 of the present invention;
[0024] Figure 1 (c) Impedance spectra of Cu in TAZ with different concentrations provided by Examples 1-4 of the present invention;
[0025] Figure 1 (d) Impedance spectra of Co in TAZ with different concentrations provided by Examples 1-4 of the present invention;
[0026] Figure 2 The Tafel curves and impedance spectra of Cu and Co in different concentrations of PO provided in Examples 5-8 of the present invention are shown;
[0027] in, Figure 2 (a) Tafel curves of Cu in different concentrations of PO provided by Examples 5-8 of the present invention;
[0028] Figure 2 (b) Tafel curves of Co in different concentrations of PO provided in Examples 5-8 of the present invention;
[0029] Figure 2 (c) Impedance spectra of Cu in different concentrations of PO provided in Examples 5-8 of the present invention;
[0030] Figure 2 (d) Impedance spectra of Co in different concentrations of PO provided in Examples 5-8 of the present invention;
[0031] Figure 3 The impedance spectra and Tafel curves of Cu and Co in PMTA with different concentrations provided by Examples 9-12 of the present invention are shown;
[0032] in, Figure 3 (a) Tafel curves of Cu in PMTA at different concentrations provided by Examples 9-12 of the present invention;
[0033] Figure 3 (b) Tafel curves of Co in PMTA at different concentrations provided by Examples 9-12 of the present invention;
[0034] Figure 3 (c) Impedance spectra of Cu in PMTA of different concentrations provided in Examples 9-12 of the present invention;
[0035] Figure 3 (d) Impedance spectra of Co in PMTA with different concentrations provided in Examples 9-12 of the present invention;
[0036] Figure 4AFM images of Cu / Co wafers after chemical mechanical polishing using the polishing solution with a composite corrosion inhibitor provided in Examples 16-20 of the present invention are shown;
[0037] in, Figure 4 (a) is the AFM image after polishing provided by Example 16 of the present invention;
[0038] Figure 4 (b) is the post-polishing AFM image provided by Example 17 of the present invention;
[0039] Figure 4 c) AFM image after polishing provided by Example 18 of the present invention;
[0040] Figure 4 (d) is the post-polishing AFM image provided by Example 19 of the present invention;
[0041] Figure 4 (e) is the post-polishing AFM image provided by Example 20 of the present invention. DETAILED DESCRIPTION
[0042] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0043] It should be noted that the “composition” and similar terms mentioned in this embodiment refer to a blend of two or more materials, which may be miscible or immiscible, and may or may not be phase-separated.
[0044] The numerical range in the present embodiment is an approximate value, so unless otherwise specified, the value outside the range can be included. Numerical range includes an infinite number of point values in the range from the lower limit to the upper limit value with a unit as an increment, provided that there are at least two unit separations between any lower limit and any upper limit. Numerical range provided by the present invention, such as 100-1000, means the point values of all unit intervals, such as 100, 101, 102, ..., 999, 1000, etc., and the sub-ranges in this numerical range, such as 100-144, 155-170, 197-200, etc. It is only an example of specific intent above, and all possible numerical combinations between the lower limit and the upper limit value listed should be regarded as the open range and protection range clearly stated in the present invention.
[0045] The terms "comprising", "including", "having" and the like mean that the composition, process, etc. are not limited to the disclosed components, steps, etc., and may also include other undisclosed components, steps, etc., while the terms "consisting of...", "being" and the like indicate that only the specified components and steps are included, and other components and steps are excluded from the scope of the specified composition, process, etc.
[0046] In a specific embodiment, the present embodiment provides a polishing liquid for chemical mechanical polishing, the polishing liquid comprising an abrasive, an oxidant, a corrosion inhibitor, a complexing agent and water;
[0047] The corrosion inhibitor includes any one of 1,2,4-triazole, potassium oleate or 1-phenyl-5-mercaptotetrazole or a combination of at least two of them.
[0048] Polishing fluid is one of the key elements in CMP technology. Its composition and performance are directly related to the material removal rate and the surface quality after polishing. In the material removal process of metal polishing, the polishing fluid has the following functions: promoting metal dissolution and increasing the removal rate; reacting with the metal to form an oxide film, reducing the metal hardness or weakening the metal bonding strength, promoting metal removal; passivating metal recesses to prevent excessive corrosion.
[0049] During the CMP process of metals, due to the presence of oxidants in the polishing liquid, a layer of oxide film with passivation properties often forms on the metal surface. This passivation film covers the metal surface, which hinders the further removal of the material to a certain extent. At the same time, the passivation film is removed under the mechanical grinding action of the abrasive particles and the polishing pad, and becomes an insoluble substance remaining in the polishing liquid. If it is not dissolved in time and carried away by the polishing liquid, it will contaminate the wafer surface and cause scratches and other damage. Therefore, an appropriate amount of complexing agent needs to be added to the polishing liquid. The reason is that the complexing agent will react with metal oxides or metal ions to form a soluble metal organic complex: it can effectively prevent the insoluble substances generated by the passivation film from polluting and damaging the surface, and can also reduce the metal ion pollution in the polishing liquid. At the same time, it also promotes the removal rate of metal materials, and improves the overall polishing efficiency of the CMP process to a certain extent.
[0050] During the CMP process of metal, since the corrosion on its surface is isotropic, that is, both the convex and concave parts of the metal surface will be corroded by various additives in the polishing liquid, it is easy to cause defects such as surface roughness, dishing and corrosion pits. Therefore, corrosion inhibitors must be added to the polishing liquid to reduce surface corrosion and improve the quality of metal surface flatness.
[0051] During the polishing process of the Cu / Co interconnect structure, since the polishing process of the Co barrier layer involves multiple materials such as copper wiring, barrier layer metal, and dielectric layer, and is the polishing of a heterogeneous interface, the removal selectivity of different materials needs to be controlled. In order to achieve the regulation of the polishing rate, this embodiment specially designs the components of the required polishing liquid for the chemical mechanical polishing operation of the Cu / Co interconnect structure, so that the removal selectivity of different materials can be controlled, so as to reduce surface corrosion, improve the metal surface flattening quality, and prevent the occurrence of defects such as surface roughness, dishing, and corrosion pits during the polishing process.
[0052] Optionally, the complexing agent includes any one of citric acid, glycine or ethylenediaminetetraacetic acid or a combination of at least two thereof; further preferably, the complexing agent is ethylenediaminetetraacetic acid, and the corrosion inhibitor is 1-phenyl-5-mercaptotetrazolyl.
[0053] It should be noted that different corrosion inhibitors have different corrosion inhibition mechanisms and exhibit different slow-release effects. 1,2,4-triazole protects Co from excessive corrosion in the form of physical adsorption on the Co surface, while its adsorption form on Cu tends to be chemical adsorption. In a polishing liquid system with potassium persulfate as the oxidant, 1,2,4-triazole is used as a corrosion inhibitor. As the concentration of 1,2,4-triazole (TAZ) increases, the corrosion inhibition efficiency of Cu and Co gradually increases, and the slow-release effect of TAZ on Cu is better than that on Co.
[0054] The adsorption of potassium oleate (PO) on Cu and Co tends to be chemical adsorption. Therefore, compared with TAZ, PO has a better corrosion inhibition effect on Cu and Co, and the ability to inhibit corrosion increases with the increase of PO concentration.
[0055] 1-phenyl-5-mercaptotetrazole (PMTA) acts on the Cu surface in the form of chemical adsorption, but it has no corrosion inhibition effect on Co. Therefore, with the increase of PMTA concentration, the slow release efficiency of Cu gradually increases, but the corrosion phenomenon of Co is not alleviated, which shows that PMTA is not enough to prevent the corrosion of Co in the polishing liquid composed of potassium persulfate (KPS) and citric acid (CA). However, it is precisely because PMTA has such a different "corrosion inhibition effect" on Co that it can protect Cu and inhibit the removal rate of Cu on the one hand; on the other hand, it can accelerate the chemical reaction of Co, making the polishing rate selection ratio of Cu / Co in an adjustable state.
[0056] During the polishing process of the Cu / Co interconnect structure, since the polishing process of the Co barrier layer involves multiple materials such as copper wiring, barrier layer metal, and dielectric layer, it is the polishing of a heterogeneous interface, so the removal selectivity of different materials needs to be controlled. In order to achieve the regulation of the polishing rate, PMTA is preferably used as a corrosion inhibitor for the chemical mechanical polishing operation of the Cu / Co interconnect structure.
[0057] It should be noted that the present invention provides a variety of optional complexing agents and a variety of optional corrosion inhibitors, which can be arbitrarily combined to form polishing liquids of different components, for example, a combination of citric acid and 1,2,4-triazole, a combination of glycine and potassium oleate, a combination of ethylenediaminetetraacetic acid and 1-phenyl-5-mercaptotetrazole, a combination of citric acid and potassium oleate, etc. The specific combinations listed above and the combinations that are not listed and can form a stable mixture all belong to the protection scope and disclosure scope of the present invention.
[0058] Optionally, the concentration of the corrosion inhibitor is 1-7 mM, for example, 1 mM, 2 mM, 3 mM, 4 mM, 5 mM, 6 mM or 7 mM; more preferably, 3-5 mM.
[0059] The corrosion inhibitor provided in this embodiment preferably uses 3-5mM PMTA. PMTA in this concentration range can suppress the material removal rate (MRR) of Cu, while the MRR of Co can be greatly improved. This special corrosion inhibition mechanism can inhibit the removal of Cu and protect Cu on the one hand, and accelerate the chemical reaction of Co on the other hand, so that the polishing rate selection ratio of Cu / Co is in an adjustable state.
[0060] Optionally, the corrosion inhibitor consists of 1-phenyl-5-mercaptotetrazole and potassium oleate; further preferably, the concentration ratio of 1-phenyl-5-mercaptotetrazole to potassium oleate is 1:(1-5).
[0061] Optionally, the oxidizing agent is potassium persulfate.
[0062] When potassium persulfate polishing liquid is used for chemical mechanical polishing, the removal process of Cu and Co simultaneously involves chemical abrasion and mechanical grinding. The two mechanisms of action play a synergistic role. Chemical abrasion generates an oxidized soft layer, which promotes the mechanical grinding effect. The transition metals produced by mechanical grinding can promote the sulfate radical SO4 ·- Specifically, in terms of chemical abrasion, potassium persulfate can release highly oxidizing sulfate free radicals SO4 through the oxidation process of transition metal Co and persulfate. ·- ; Subsequently, sulfate radical SO4 ·- The low-valent Co can be converted into high-valent Co to form an oxidized soft layer, thereby promoting mechanical grinding. In terms of mechanical grinding, the ground Co can promote SO4 ·- The production of ions increases their concentration, which in turn promotes abrasion through wear and increases the material removal rate.
[0063] It should be noted that this embodiment does not impose any specific requirements or restrictions on the abrasive. By way of example, colloidal silica can be selected as the abrasive of the polishing liquid.
[0064] Colloidal silica is preferably prepared by hydrolyzing alkoxysilane to obtain silica particles free of impurities. In addition, colloidal silica can also be prepared by eliminating alkali metals in an aqueous solution of alkali metal silicates, but this preparation method causes the alkali metals remaining in the particles to be gradually washed out, thereby adversely affecting the polishing performance. From this point of view, colloidal silica is more preferably prepared by hydrolyzing alkoxysilane.
[0065] The diameter of the silica particles in the colloidal silica can be appropriately selected according to the intended application of the abrasive grains, and is generally in the range of about 10 nm to 200 nm. In one embodiment, the diameter of the silica particles is 40 to 80 nm, preferably 60 nm.
[0066] Optionally, the pH value of the polishing liquid is 9.5-11, for example, it can be 9.5, 9.6, 9.7, 9.8, 9.9, 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9 or 11.
[0067] The polishing liquid provided in this embodiment should have a pH value in the range of 9.5-11, and preferably in the range of 10-10.5. In order to adjust the pH value to the above required range, a base can be used as a pH adjuster.
[0068] It should be noted that the present invention does not make any specific requirements or special restrictions on the type of base, and it can be, for example, ammonia, organic ammonium hydroxide (such as ammonium hydroxide and tetramethylammonium hydroxide), non-metallic alkaline reagents (such as diethanolamine, triethanolamine and triisopropanolamine) or alkali metal hydroxides (such as potassium hydroxide and lithium hydroxide, etc.). Among the various types of bases listed above, ammonium hydroxide, potassium hydroxide, lithium hydroxide or tetramethylammonium hydroxide is preferably used.
[0069] It should be noted that the present invention does not make any specific requirements or special limitations on the amount of pH adjuster added. The pH value of the final polishing liquid is within the range of 9.5-11. The amount of pH adjuster added can be determined as any amount that maintains the pH value within the desired range.
[0070] This embodiment does not make specific requirements and special restrictions on the preparation method of the polishing liquid. The screened abrasive, oxidant, complexing agent and corrosion inhibitor can be dissolved or dispersed in an aqueous medium, especially deionized water. For this purpose, conventional and standard mixing methods and mixing equipment can be used, such as a stirred tank, an online dissolver, a high-shear high-speed mixer, an ultrasonic mixer, a homogenizer nozzle or a convection mixer. The mixed liquid is filtered through a filter with appropriate mesh to remove coarse granular particles, and finally the polishing liquid for chemical mechanical polishing provided in this embodiment is obtained.
[0071] In another specific embodiment, this embodiment provides a chemical mechanical polishing method, the chemical mechanical polishing method comprising:
[0072] The above-mentioned polishing liquid is spread on the surface of the polishing pad, the carrier head presses the wafer onto the polishing pad and drives the wafer to rotate, and the copper interconnection cobalt barrier layer structure of the wafer is chemically mechanically polished under the action of the polishing liquid.
[0073] Specifically, the chemical mechanical polishing process of the graphic sheet is divided into three steps:
[0074] (1) The rough polishing stage of Cu is to quickly remove the Cu covering layer on the pattern piece and expose the wafer interconnection lines;
[0075] (2) The purpose of the Cu / Co barrier layer fine polishing stage is to remove the Co barrier layer under the copper film and stop the polishing on the dielectric layer. It should be noted that in this stage, the exposed copper film and the Co barrier layer need to be polished at the same time, which belongs to the polishing of the heterogeneous interface. In order to avoid the occurrence of defects such as copper dishing, the polishing rate of the copper film is required to be slightly lower, and the polishing rate of the Co barrier layer is slightly higher, but the difference between the two rates is not large, and should be close to 1:1. In order to ensure the material removal selectivity during heterogeneous interface polishing, a special barrier layer polishing liquid should be selected at this stage.
[0076] (3) The post-CMP cleaning process of the graphic wafer is mainly aimed at cleaning the particles remaining on the wafer surface after polishing.
[0077] Both step (1) and step (2) need to be carried out under the action of a polishing liquid, but the polishing liquids used in step (1) and step (2) are different. The rough polishing liquid used in step (1) can optionally include an abrasive, an oxidant, a complexing agent and water. Among them, the abrasive can be colloidal silica, and the oxidant can be selected from any one or a combination of at least two of hydrogen peroxide, peracetic acid, potassium persulfate or ammonium persulfate, preferably potassium persulfate. The complexing agent is selected from any one or a combination of at least two of citric acid, glycine or ethylenediaminetetraacetic acid; preferably glycine. The pH value of the rough polishing liquid is adjusted to 10-11 by a pH regulator.
[0078] The fine polishing liquid used in step (2) can optionally use the polishing liquid provided in this embodiment, that is, it includes an abrasive, an oxidant, a corrosion inhibitor, a complexing agent and water, wherein the abrasive can be colloidal silica, and the oxidant can be selected from any one or a combination of at least two of hydrogen peroxide, peracetic acid, potassium persulfate or ammonium persulfate, preferably potassium persulfate. The corrosion inhibitor can be selected from any one or a combination of at least two of 1,2,4-triazole, potassium oleate or 1-phenyl-5-mercaptotetrazole; preferably 1-phenyl-5-mercaptotetrazole. The complexing agent is selected from any one or a combination of at least two of citric acid, glycine or ethylenediaminetetraacetic acid; preferably citric acid. The pH value of the fine polishing liquid is adjusted to 10-11 by a pH regulator.
[0079] Optionally, during the chemical mechanical polishing process, the rotation speed of the polishing pad is 90-100rpm, for example, it can be 90rpm, 91rpm, 92rpm, 93rpm, 94rpm, 95rpm, 96rpm, 97rpm, 98rpm, 99rpm or 100rpm; the rotation speed of the carrier head is 80-90rpm, for example, it can be 80rpm, 81rpm, 82rpm, 83rpm, 84rpm, 85rpm, 86rpm, 87rpm, 88rpm, 89rpm or 90rpm.
[0080] Examples 1-4
[0081] Silica sol abrasive, oxidant potassium persulfate (KPS), complexing agent citric acid (CA) and corrosion inhibitor 1,2,4-triazole (TAZ) were weighed / measured respectively, and mixed according to the proportions of each component provided in Table 1 to obtain the corresponding polishing solution.
[0082] Table 1
[0083] Example No. Silica sol abrasive Oxidant KPS Complexing agent CA Corrosion Inhibitor TAZ Example 1 3vol.% 10mM 5mM 1mM Example 2 3vol.% 10mM 5mM 3mM Example 3 3vol.% 10mM 5mM 5mM Example 4 3vol.% 10mM 5mM 7mM
[0084] Electrochemical experiments were carried out on the polishing liquid prepared in Examples 1-4 to verify the corrosion inhibition effect of TAZ. The instrument used in the electrochemical experiment was the Autolab electrochemical workstation of Metrohm Company of Switzerland. The system used in the experiment was a three-electrode system, consisting of a working electrode (Cu electrode, Co electrode, purity of both above 99.95%, the working surface metal column diameter is 5 mm and encapsulated in epoxy resin), a counter electrode (platinum sheet electrode) and a reference electrode (saturated calomel electrode).
[0085] The Tafel curve was measured by linear voltammetry. Figure 1 The equivalent impedance of the metal-solution interface was measured by electrochemical impedance spectroscopy. The measurement results are shown in Table 2.
[0086] Table 2
[0087]
[0088] From the data in Table 2, it can be seen that as the concentration of TAZ increases from 1mM to 7mM, the polarization impedance of the Cu and Co electrodes increases successively. Figure 1 The Tafel curve provided can be fitted to obtain the corrosion current density of the two metals. The calculation results are shown in Table 2. Among them, the corrosion current density of Cu increases from 19.5 μA·cm 2 Reduced to 1.2 μA·cm 2 , the corrosion current density of Co increased from 11.1 μA·cm 2 Reduced to 5.5μA·cm 2 . According to calculation, the corrosion inhibition efficiency of 1mM, 3mM, 5mM, and 7mM TAZ on Cu is 8.9%, 46.3%, 82.7%, and 94.4%, respectively; the corrosion inhibition efficiency on Co is 6.7%, 12.6%, 23.5%, and 53.8%, respectively. Overall, the corrosion inhibition effect of TAZ on Cu is better than that on Co, and the higher the concentration, the stronger the corrosion inhibition effect.
[0089] The polishing liquid prepared in Examples 1-4 was used to perform chemical mechanical polishing experiments on wafers. In the experiments, 2-inch Cu wafers and Co wafers produced by SKW were used, wherein the Cu wafer was polished using the ECP process. The Ta film is deposited on the wafer with a thickness of about 1.5 μm; the Co wafer is deposited on the wafer using the CVD process. The TiN film is deposited on a surface with a thickness of about 90 nm.
[0090] After polishing, the thickness of the Cu and Co wafer metal films was measured using a four-probe device. During the measurement process, 21 points in the wafer diameter direction were selected to measure the metal film resistance. The metal film thickness of the 21 points was calculated using the formula provided by the system, and the average was taken as the wafer film thickness. By measuring the thickness of the Cu and Co films before polishing, the corresponding material removal rate can be calculated, and the calculation results are shown in Table 3.
[0091] Table 3
[0092]
[0093] Embodiment 5-8
[0094] Silica sol abrasive, oxidant potassium persulfate (KPS), complexing agent citric acid (CA) and corrosion inhibitor potassium oleate (PO) were weighed / measured respectively, and mixed according to the distribution ratio of each component provided in Table 4 to obtain the corresponding polishing liquid.
[0095] Table 4
[0096] Example No. Silica sol abrasive Oxidant KPS Complexing agent CA Corrosion inhibitor PO Example 5 3vol.% 10mM 5mM 1mM Example 6 3vol.% 10mM 5mM 3mM Example 7 3vol.% 10mM 5mM 5mM Example 8 3vol.% 10mM 5mM 7mM
[0097] Electrochemical experiments were conducted on the polishing liquids prepared in Examples 5-8 to verify the corrosion inhibition effect of the corrosion inhibitor PO. The experimental process and conditions were referenced to Examples 1-4. The Tafel curves obtained by measurement were as follows: Figure 2 The measurement results are shown in Table 5.
[0098] Table 5
[0099]
[0100] From the data in Table 5, it can be seen that except for the Co electrode, the change in 1mM and 3mM PO concentrations is not obvious. As the PO concentration increases, the impedance of the two metals still increases. Figure 2 The Tafel curve provided can be fitted to obtain the corrosion current density of the two metals. The calculation results are shown in Table 5. Among them, with the increase of PO concentration, the corrosion current density of Cu increases from 10.3 μA·cm 2 Reduced to 0.8μA·cm 2 , the corrosion current density of Co increased from 5.2 μA·cm 2 Reduced to 0.4μA·cm 2 . It was calculated that the corrosion inhibition efficiency of 1mM, 3mM, 5mM, and 7mM PO on Cu was 51.9%, 91.1%, 93.9%, and 96.3%, respectively; the corrosion inhibition efficiency on Co was 56.3%, 79.8%, 92.4%, and 96.6%, respectively. Compared with TAZ, PO has a better corrosion inhibition effect on Cu and Co, and as the PO concentration increases, the ability to inhibit corrosion also increases.
[0101] The polishing liquid prepared in Examples 5-8 was used to perform chemical mechanical polishing experiments on the wafer. The experimental process and conditions were the same as those in Examples 1-4. The material removal rates of Cu and Co were calculated. The calculation results are shown in Table 6.
[0102] Table 6
[0103]
[0104] Examples 9-12
[0105] Silica sol abrasive, oxidant potassium persulfate (KPS), complexing agent citric acid (CA) and corrosion inhibitor 1-phenyl-5-mercaptotetrazole (PMTA) were weighed / measured respectively, and mixed according to the distribution ratio of each component provided in Table 7 to obtain the corresponding polishing solution.
[0106] Table 7
[0107] Example Silica sol abrasive Oxidant KPS Complexing agent CA PMTA corrosion inhibitor Example 9 3vol.% 10mM 5mM 1mM Example 10 3vol.% 10mM 5mM 3mM Embodiment 11 3vol.% 10mM 5mM 5mM Example 12 3vol.% 10mM 5mM 7mM
[0108] Electrochemical experiments were conducted on the polishing liquids prepared in Examples 9-12 to verify the corrosion inhibition effect of the corrosion inhibitor PMTA. The experimental process and conditions were as shown in Examples 1-4. The Tafel curves obtained by measurement are as follows: Figure 3 The measurement results are shown in Table 8.
[0109] Table 8
[0110]
[0111]
[0112] From the data in Table 8, it can be seen that the variation of Cu is similar to the corrosion inhibition effect of TAZ and PO, that is, the corrosion inhibition effect increases with the increase of corrosion inhibitor concentration. As the concentration of PMTA increases from 1mM to 7mM, the corrosion current density of Cu increases from 0.8μA·cm 2 Reduced to 0.1 μA·cm 2 , the corrosion inhibition efficiency increased from 96.3% to 99.5%. The difference is that with the increase of PMTA concentration, the corrosion phenomenon of Co electrode was not alleviated, and even when the PMTA concentration was 3mM (Example 10) or 5mM (Example 11), the current corrosion density of Co was much higher than that without PMTA, which shows that PMTA is not enough to prevent the corrosion of Co in the polishing solution composed of KPS and CA.
[0113] The polishing liquid prepared in Examples 9-12 was used to perform chemical mechanical polishing experiments on the wafers. The experimental process and conditions were the same as those in Examples 1-4. The material removal rates of Cu and Co were calculated. The calculation results are shown in Table 9.
[0114] Table 9
[0115]
[0116] From the removal rate data provided in Table 3, Table 6 and Table 9, it can be seen that TAZ (Table 3) and PO (Table 6) have a certain inhibitory effect on the MRR of Cu and Co, and the polishing rate of Cu is higher than that of Co, which easily produces defects such as Cu dishing that affect the interconnection performance, so TAZ and PO do not play a protective role in the CMP process of Cu / Co interconnection structure. When PMTA is used as a corrosion inhibitor in the polishing solution (Table 9), the MRR of Cu is suppressed, while the MRR of Co is greatly improved.
[0117] Combining the electrochemical test results and chemical mechanical polishing test results, it can be found that TAZ and PO can effectively prevent the corrosion of Cu and Co, and the higher the concentration, the higher the slow release efficiency. PMTA can effectively prevent the corrosion of Cu, but it is not enough to prevent the corrosion of Co, especially when the concentration of PMTA is 5mM. It is precisely because PMTA has a completely different "corrosion inhibition effect" from TAZ and PO that it can protect Cu (inhibit the removal of Cu) on the one hand, and accelerate the chemical reaction of Co on the other hand, inhibiting the MRR of Cu while increasing the MRR of Co, making the polishing rate selection ratio of Cu / Co in an adjustable state. Therefore, compared with TAZ and PO, PMTA is more suitable for chemical mechanical polishing of Cu / Co interconnect structures.
[0118] Examples 13-15
[0119] Examples 13-15 explored which combination of the corrosion inhibitor PMTA and the complexing agent is more suitable for the fine polishing process of the Cu / Co interconnect structure.
[0120] Four polishing liquids with different components were prepared respectively, and recorded as polishing liquid A, polishing liquid B, polishing liquid C and polishing liquid D. The components of each polishing liquid are shown in Table 10.
[0121] Table 10
[0122] Polishing fluid number Silica sol abrasive KPS Complexing agent PMTA Polishing liquid A 3vol.% 10mM 5mM GLY — Polishing liquid B 3vol.% 10mM 5mM CA 5mM Polishing liquid C 3vol.% 10mM 5mM GLY 5mM Polishing liquid D 3vol.% 10mM 5mM EDTA 5mM
[0123] Table 11
[0124] Example No. Cu rough polishing Cu / Co fine polishing Embodiment 13 Polishing liquid A Polishing liquid B Embodiment 14 Polishing liquid A Polishing liquid C Embodiment 15 Polishing liquid A Polishing liquid D
[0125] As shown in Table 11, in Examples 13-15, polishing liquid A was used as a rough polishing liquid, and polishing liquid B, polishing liquid C, and polishing liquid D were used as fine polishing liquids, respectively, to perform rough polishing and fine polishing on the Cu / Co wafers. The removal rates of the Cu / Co wafers after polishing were measured, and the removal rates of Cu and Co were calculated, and the results are shown in Table 12.
[0126] Table 12
[0127]
[0128] From the removal rate data provided in Table 12, it can be seen that the polishing liquid C (Example 14) containing GLY makes the removal rate of Cu much higher than the removal rate of Co, which is not conducive to the surface flattening of Cu / Co wafers. Both polishing liquid B (Example 14) and polishing liquid D (Example 15) can make the removal rate of Co higher than the removal rate of Cu, among which, the polishing liquid D (Example 15) containing EDTA can make the MRR of Co higher than the MRR of Cu while satisfying the removal selectivity of both close to 1:1, which is due to the interaction between the high Cu / Co selectivity of EDTA and the slow release characteristics of PMTA (increasing Co MRR while suppressing Cu MRR). Therefore, this embodiment preferably uses the complexing agent EDTA and the corrosion inhibitor PMTA to be more suitable for the fine polishing process of Cu / Co wafers.
[0129] Examples 16-20
[0130] Examples 16-20 explore the optimal concentration range of the compound corrosion inhibitor. Based on the test results of Examples 13-15, EDTA was selected as the complexing agent, and PMTA with excellent removal rate and corrosion inhibitor PO were selected as the compound corrosion inhibitor. The corresponding fine polishing liquid was prepared according to the polishing liquid ratio provided in Table 13.
[0131] Table 13
[0132]
[0133]
[0134] Table 14
[0135] Example No. Cu rough polishing Cu / Co fine polishing Example 16 Polishing liquid A Polishing liquid E Embodiment 17 Polishing liquid A Polishing liquid F Embodiment 18 Polishing liquid A Polishing liquid G Embodiment 19 Polishing liquid A Polishing liquid H Embodiment 20 Polishing liquid A Polishing liquid I
[0136] As shown in Table 14, in Examples 16-20, polishing liquid A was used as a rough polishing liquid, and polishing liquid E, polishing liquid F, polishing liquid G, polishing liquid H, and polishing liquid I provided in Table 13 were used as fine polishing liquids, respectively, to perform rough polishing and fine polishing on the Cu / Co wafers in sequence. The removal rate of the Cu / Co wafers after polishing was measured, and the removal rates of Cu and Co were calculated, and the results are shown in Table 15.
[0137] Table 15
[0138]
[0139] It can be seen from the removal rate data provided in Table 15 that in Example 16 and Example 20, the post-polishing removal rate of Cu / Co is significantly higher than that of Co / Cu. Excessive difference in the removal rates between the two will cause defects such as dished pits on the wafer surface, which is not conducive to the flattening of the wafer surface. In Examples 17-19, the removal rate of Co is slightly higher than the process requirement of the removal rate of Co, which is more suitable for the fine polishing stage of Cu and Co wafers. Therefore, this embodiment preferably uses PMTA and PO to be compounded according to a concentration ratio of 1: (1-5).
[0140] Figure 4 AFM images of the polished wafers provided for Examples 16-20 are provided by Figure 4 It can be seen that Figure 4 (a) (Example 16) has more residual particles; Figure 4 In (b)-(d) (Examples 17-19), the number of particles on the wafer surface after polishing is relatively small, and it shows a decreasing trend as the concentration of the compound corrosion inhibitor increases; Figure 4 (e) (Example 20) The number of organic residual particles on the wafer surface increases. This is because the adsorption behavior of organic corrosion inhibitors on the metal surface can be characterized by the adsorption isotherm. The smaller the absolute value of the adsorption Gibbs free energy, the easier it is to clean the organic slow-release particles remaining on the metal surface. Therefore, the role of the corrosion inhibitor on the wafer surface is analyzed by calculating the adsorption Gibbs free energy. ads are -27.4935 kJ / mol and -27.2292 kJ / mol respectively. The ΔG of PMTA on the Cu surface ads 0 =-33.671 kJ / mol. When PO is introduced into PMTA for compounding, the synergistic effect of the two can reduce the high adsorption capacity of PMTA for Cu and Co, making it easier to clean and reducing the residual particles on the surface. However, when the concentration of the corrosion inhibitor introduced is too high, it will cause particles to aggregate on the wafer surface, resulting in too many residual surface particles. Therefore, the optimal concentration ratio range of PMTA and PO in the compound corrosion inhibitor provided in this embodiment is 1: (1-5).
[0141] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polishing liquid for chemical mechanical polishing of a copper interconnect cobalt barrier structure of a wafer, characterized in that: The polishing liquid comprises an abrasive, an oxidant, a corrosion inhibitor, a complexing agent and water; The oxidant is potassium persulfate, the corrosion inhibitor is composed of 1-phenyl-5-mercaptotetrazole and potassium oleate with a concentration ratio of 1:(1-5), and the complexing agent includes any one of citric acid or ethylenediaminetetraacetic acid or a combination of two, so that the material removal rate of cobalt is higher than that of copper, and the polishing rate selection ratio of copper / cobalt is in an adjustable state.
2. The polishing liquid according to claim 1, characterized in that The complexing agent is ethylenediaminetetraacetic acid, so that the removal selectivity ratio of cobalt and copper is close to 1:
1.
3. The polishing liquid according to claim 1, characterized in that The pH value of the polishing liquid is 9.5-11.
4. The polishing liquid according to any one of claims 1 to 3, characterized in that: The concentration of the corrosion inhibitor is 1-7 mM.
5. A chemical mechanical polishing method, characterized in that: The chemical mechanical polishing method comprises: The polishing liquid as described in any one of claims 1 to 4 is spread on the surface of the polishing pad, the carrier head presses the wafer onto the polishing pad and drives the wafer to rotate, and the copper interconnection cobalt barrier layer structure of the wafer is chemically mechanically polished under the action of the polishing liquid.
6. The chemical mechanical polishing method according to claim 5, characterized in that: During the chemical mechanical polishing process, the rotation speed of the polishing pad is 90-100 rpm, and the rotation speed of the carrier head is 80-90 rpm.
Citation Information
Patent Citations
Chemical mechanical polishing solution for barrier layer planarization, and use method thereof
CN104745088A